On properties of fuzzy ideals in po-semigroup - Kumar Majumder Samit; Kumar Sardar Sujit (National Academy of Sciences of Armenia)
In this paper some properties of fuzzy ideals and fuzzy ideal extensions in a po-semigroup have been investigated.
Keywords: Mathematical logic and foundations; General algebraic systems; Group theory and generalizations